EXPRESSION OF SUBJECTIVE ATTITUDE IN A SCIENTIFIC TEXT (IN ENGLISH AND UZBEK LANGUAGES) - Sobirova Intizor Muhammatkulovna (World Scientific Research Journal, 2025)
Abstract: This article examines how subjective attitude is expressed in Uzbek and English Linguistics. The speaker’s attitude toward reality is indicated by their use of words such as "caress," "respect," "belittling," "modest," "cursing," and "teasing," as well as instances of "exaggerating," "amplifying," and "emphasizing." The entire statement or a portion of it expresses the meanings indicated feelings in the context. As we discussed below, subjective attitude is an expression of the speaker’s attitude toward reality and his words, whether it be positive or negative. It is quite frequent in the Uzbek and English languages as well as other languages to express the subjective meanings of decreasing, belittling, caressing, glorifying, and strengthening with the aid of numerous affixes - morphemes.